2019
DOI: 10.1007/s13205-019-1587-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of the polyphenol oxidase gene in response to signaling molecules, herbivory and wounding in antisense transgenic tobacco plants

Abstract: Key message We provide evidence that the expression of the PPO gene was significantly reduced in response to wounding, MeJ and herbivory in transgenic tobacco under wound-inducible OsRGLP2 promoter in an anti-sense orientation. Abstract Polyphenol oxidase (PPO) genes play an important role in plant defense mechanisms against biotic and abiotic stresses. In the present study, a 655 bp core sequence of the potato PPO gene was placed under the control of wound-inducible OsRGLP2 promoter in an anti-sense direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…In tomato plants, induction of antisense PPO cDNA induces resistance in plants to pathogen Pseudomonas syringae that results in down-regulation of ppo gene family members [72]. The expression of PPO gene was considerably decreased in response to wounding, MeJ and herbivory in transgenic tobacco [73]. Our study revealed the presence of two PPO DEGs (c49788_g1; c52742_g1) in Tyr metabolism pathway were down-regulated.…”
Section: Discussionmentioning
confidence: 83%
“…In tomato plants, induction of antisense PPO cDNA induces resistance in plants to pathogen Pseudomonas syringae that results in down-regulation of ppo gene family members [72]. The expression of PPO gene was considerably decreased in response to wounding, MeJ and herbivory in transgenic tobacco [73]. Our study revealed the presence of two PPO DEGs (c49788_g1; c52742_g1) in Tyr metabolism pathway were down-regulated.…”
Section: Discussionmentioning
confidence: 83%
“…and Glycine Max were significantly induced [19,35]. Furthermore, transcriptome verified that PtrPPO13 was significantly up-regulated and PtrPPO11/14/15 was significantly inhibited under damage and mechanical damage of Poplar Beetle (Figure 6b).…”
Section: Expression Profile Of Populus Ppos Gene In Answer To Diversementioning
confidence: 88%
“…Furthermore, transcriptome verified that PtrPPO13 was significantly up-regulated and PtrPPO11/14/15 was significantly inhibited under damage and mechanical damage of Poplar Beetle (Figure 6b). MeJA have been involved in the signal transduction of insect bites and mechanical damage to plants [18,19]. Moreover, elements of MeJA-responsiveness were identified on the promoter of PtrPPO13.…”
Section: Expression Profile Of Populus Ppos Gene In Answer To Diversementioning
confidence: 99%
“…NtSOD and NtPOD activities are known to be regulated at their transcription levels [ 51 ]. NtPPO is a polyphenol oxidase gene involved in stress tolerance in many plants [ 52 ]. NtNECD1 plays an important role in ABA biosynthesis [ 53 ].…”
Section: Discussionmentioning
confidence: 99%